Combined activity of Maruca vitrata multi-nucleopolyhedrovirus, MaviMNPV, and oil from neem, Azadirachta indica Juss and Jatropha curcas L., for the control of cowpea pests. (June 2015) - Sokame, Bonoukpoè Mawuko; Tounou, Agbéko Kodjo; Datinon, Benjamin; Dannon, Elie Ayitondji; Agboton, Cyriaque; Srinivasan, Ramasamy; Pittendrigh, Barry Robert; Tamò, Manuele
Abstract: The insecticidal activity of Maruca vitrata (F.) multi-nucleopolyhedrovirus ( Mavi MNPV) combined with oil from neem, Azadirachta indica Juss and Jatropha curcas L. (Euphorbiaceae) was studied under laboratory and field conditions against three key insect pests of cowpea, Vigna unguiculata (L.) Walp. Second-instar Aphis craccivora Koch and Megalurothirps sjostedti Trybom nymphs, and third-instar M. vitrata larvae, all from laboratory colonies, were treated with various concentrations of one of the control agents separately or combined. Daily mortality was recorded for five days ( A. craccivora and M. sjostedti nymphs) or fourteen days ( M. vitrata ) and the larval and pupal development as well as adult emergence were assessed. Combination of Mavi MNPV resulted in a significantly higher larval mortality in M. vitrata than treatment with either virus or botanical insecticide alone at the corresponding concentrations. Larvae of M. vitrata infected with Mavi MNPV and treated with botanical oils died sooner than those infected with only one control agent. Combinations of Mavi MNPV and botanical oils produced additive or synergistic effects. No evidence of antagonistic effects was noted. In field experiments, the application of botanical insecticide and Mavi MNPV either alone or in combination was effective in reducing insect abundance over the four weeks, and preventing yield loss. In the first field season, where the M. vitrata population was higher, the combination of the virus and either of the botanical pesticides induced significantly higher yields than spraying chemical insecticide. Application of Mavi MNPV in combination with J. curcas and A. indica oil has proven to induce consistent Mavi MNPV infection in M. vitrata populations. The combined application of Mavi MNPV and botanical oils is discussed in the context of integrated pest management. Highlights: We compared botanical and viral bio-pesticides against cowpea pests. Mixtures induced higher larval mortality in target organisms than sole products. Damage and yield data from field experiments confirmed lab observations. Prevalence of viral bio-pesticide was high in treated pod borer populations.